Evaluation of the thermal, mechanical and dynamic mechanical characteristics of modified graphite nanoplatelets and graphene oxide high-density polyethylene composites. (1st January 2018) - Lin, Sean; Anwer, Muhammad A.S.; Zhou, Yannan; Sinha, Apoorv; Carson, Luke; Naguib, Hani E.
Abstract: The effectiveness of graphitic nanoplatelets (GNPs) and graphene oxide (GO) as reinforcing fillers in a high-density polyethylene (HDPE) matrix was evaluated based on morphological, tensile, dynamic mechanical, and thermal property improvements over the neat polymer. Simple melt compounding and injection moulding were used for sample fabrication. Filler loadings ranged from 0.1% to 10% for GNP, and 0.05%–1.5% for GO. Improvements in mechanical properties were observed in both composites for all investigated filler loadings, though more pronounced in the GNP composites, which saw a 56% increase in elastic modulus and 23% increase in maximum stress over neat HDPE for the 10% GNP composite. A slight increase in crystallization temperature was observed for the GNP composites, while a similar drop in melting point was recorded for both systems. SEM imaging revealed that agglomeration was present in both composites, though dispersion was better for the GNP/HDPE composites.